The European Arrest Warrant in Designer Drugs Cases: with or Without Verification of Double Criminality? - Zając, Dominik (European journal on criminal policy and research, 2023)
The cross-border character of the designer drugs crimes forced the UE countries to cooperate in criminal prosecution. At first sight, in European Union law, there are proper instruments to enforce such cooperation. The Framework Decision on the European Arrest Warrant introduces the model of cross-border prosecution and abandons the requirement of double criminality in case of the group of the 32 crimes, listed in the Article 2 (2) of the FD EAW. The question is whether such a simple variant of EAW (without checking double criminality) may be enforced in designer drug cases. The work presents an argumentation that the normative meaning of Article 2 (2) of the FD EAW has to be established under European and international law. As long as a particular new drug is not internationally recognized as ‘psychotropic substance’ or ‘narcotic drug’, its trafficking cannot be treated as one of the 32 crimes, mentioned above.